Controle de Helicoverpa armigera (Hübner) (Lepideptera: Noctuidae) na cultura da soja com diferentes inseticidas, volumes e pontas de pulverização - Barboza, Julio Cesar Lengler (2015)
Currently, there is few information about the management of Helicoverpa armigera with insecticides on soybean. Thereby, the aim of this study was to verify the efficiency of insecticides in the control of Helicoverpa armigera on soybean. The insecticides Clorantraniliprole (Premio® 200 SC) 50 mL.ha-1, Flubendiamide (Belt® 480 SC) 70 mL.ha-1, Indoxacarbe (Avatar®) 400 mL.ha-1, Espinosade (Tracer®) 70 mL.ha-1, and Clorfenapir (Pirate®) 1000 mL.ha-1 were evaluated. Treatments were sprayed on 50 m² plots with a CO2 pressurized backpack sprayer. Subsequently, leaves were collected in each plot at zero, 5, 10, 15, and 20 days after spraying, and were used to feed caterpillars. As new leaves were collected, another group of second- instar caterpillars was used to determine the residual effects of the insecticides tested. The evaluations in the laboratory were performed at 3, 7, and 10 days after the beginning of the feeding. The experiment was organized in a randomized complete block design, factorial 6x5, with 20 repetitions of one caterpillar each. The insecticide Clorfenapir had the greater shock effect, and the insecticides Clorantraniliprole and Flubendiamide had the longer-lasting residual effect when compared to the insecticides Indoxacarbe and Clorfenapir. All the insecticides evaluated were efficient to control H. armigera, except the insecticide Espinosade.